Синтез обобщенных оценок состояния информационных блоков медицинских систем на примере сердечно- сосудистой системы - Мащенко, Татьяна Георгиевна; Шматок, Т. А. (НТУ "ХПИ", 2008)
В статті наведено аргументи необхідності впровадження нових методів синтезу узагальнених оцінок стану інформаційного блоку, що формується на первинних інформаційних показниках. Наведені різні методи отримання вагових коефіцієнтів для аналізу біологічних систем. Представлена загальна схема синтезу вагових коефіцієнтів та функції стану серцево-судинної системи.

The arguments of necessity to adopt new methods of synthesis the generic assessment of state of information block, which was formed on the primary information indices were drawn in the article. The different methods of the acquisition the weighting coefficients were drawn for the analyzing biologic system. The general scheme of synthesis of the weighting coefficients and function of state of cardiovascular system was presented.
Keywords: биологические системы; первичные показатели; многопараметрическое пространство; иерархическая свертка; информационные показатели; иерархическая система; весовые коэффициенты